2014
DOI: 10.19030/cier.v7i2.8489
|View full text |Cite
|
Sign up to set email alerts
|

Civility In The University Classroom: An Opportunity For Faculty To Set Expectations

Abstract: This research examines the types of uncivil behaviors frequently encountered in university classrooms. These behaviors range from walking in late to class, texting in class, and/or unprofessional emails. These behaviors can often undermine a professors teaching. Setting reasonable and consistent expectations is a combination of university policy, faculty enforcement, and possibly even input from students. While it is understood that we live in a digitally connected world, there is an opportunity for professors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…We explain that this comprises a graded assignment in the course called "Humanity," and it is worth 5% of the course score. To model good behavior (Schroeder & Robertson, 2008), we convey that the policy also protects the student by delineating expectations and responsibilities for the faculty (Ward & Yates, 2014) that include grading their work quickly, attending office hours, arriving on time to class, and offering academic and career assistance and mentorship. We explain that the Humanity homework begins at a 100% score but is reduced by 10% for each violation of the policy.…”
Section: A Course Policy To Mitigate Narcissistic Behaviors In the Business Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…We explain that this comprises a graded assignment in the course called "Humanity," and it is worth 5% of the course score. To model good behavior (Schroeder & Robertson, 2008), we convey that the policy also protects the student by delineating expectations and responsibilities for the faculty (Ward & Yates, 2014) that include grading their work quickly, attending office hours, arriving on time to class, and offering academic and career assistance and mentorship. We explain that the Humanity homework begins at a 100% score but is reduced by 10% for each violation of the policy.…”
Section: A Course Policy To Mitigate Narcissistic Behaviors In the Business Classroommentioning
confidence: 99%
“…Ideally, this policy would be supported and reinforced at the departmental and business college levels (Bergman et al, 2010) by developing a business college honor code (Ward & Yates, 2014) and promoting service projects in the curriculum to enhance empathy and deemphasize materialism (Bergman et al, 2010;Westerman et al, 2016). Religious institutions would reflect on their values and be sure that they are conveying intrinsic religiosity in the classroom and the world.…”
Section: Professor Humanity and Decorum Statementmentioning
confidence: 99%
“…They are slowly formed and rooted throughout adulthood. Many studies [ 23 , 25 , 26 ] have recommended strategies to help students learn the values of right and wrong behavior and ethical standards of the nursing profession. Ward and Yates [ 25 ] suggested using the freshman orientation or course syllabi to explain policies regarding their code of conduct and civility policies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies [ 23 , 25 , 26 ] have recommended strategies to help students learn the values of right and wrong behavior and ethical standards of the nursing profession. Ward and Yates [ 25 ] suggested using the freshman orientation or course syllabi to explain policies regarding their code of conduct and civility policies. Another suggestion was for nursing faculty members to act as role models by exercising good listening, interpersonal skills, and respectful attitudes because students can learn civil behavior by observing faculty role models [ 2 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akman (2011) found that concern for society and common good were antecedent to civility and reaching common ground during discussions facilitates civility in online forums (Lampe et al, 2014). Similarly, Ward and Yates (2014) held that serving the common good helps facilitate civility in the university classroom.…”
Section: Antecedentsmentioning
confidence: 98%